First report of a 16SrIII-L phytoplasma associated with frogskin disease in cassava (Manihot esculenta Crantz) in Brazil - Oliveira, Saulo Alves Santos de; Abreu, E.F.M.; Araújo, TS; Oliveira, EJ; Andrade, EC; García, J.M.P.; Álvarez, E. (Scientific Societies, 2014)
Cassava (Manihot esculenta Crantz) is a major staple crop in developing countries and a large source of raw material for industrial purposes as flour, starch, and ethanol. In July 2012, 24 cassava genotypes (corresponding to 1.85% of the accessions) with typical symptoms of frogskin disease (CFSD) were observed in one of the maintenance areas of the Brazilian Cassava Germplasm (located at Embrapa Cassava & Fruits, Cruz das Almas, Bahia State, Brazil). All diseased plants were asymptomatic on the aboveground parts (leaves and stem). However, for accessions BGM 880, BGM 1094, BGM 1100, BGM 1212, BGM 1218, and BGM 1526, all roots showed a woody appearance, thickened cork-like peel with opaque aspect, and coalescent lip-like slits in a honeycomb pattern. Based on literature description, two pathogens could be associated with CFSD: a dsRNA virus (belonging to family Reoviridae) and a 16SrIII-L phytoplasma (1). To investigate the presence of phytoplasma associated with the CFSD symptoms, total DNA was extracted from 0.5 g of root tissue collected from both symptomatic and asymptomatic roots by scratching the secondary vessel at the center of the cassava root with a CTAB method. The nested PCR was carried out using phytoplasma-specific primer set P1/Tint followed by R16F2n/R16R2, targeting the 16S rRNA gene sequence of 1.2 kb in length, for the final reaction (4). No phytoplasma was detected in asymptomatic cassava roots that were sampled from the same field. A posterior extraction of total RNA was made but no dsRNA was noticed on the agarose gel, and reaction of RT-PCR with specific primers (2) had no amplification. In order to characterize the strains, the 1.2-kb amplicon was digested with BamHI, MseI, MspI, KpnI, and TaqI endonucleases. The resulting patterns indicated that the symptomatic accessions were infected with a phytoplasma belonging to the 16SrIII group, sharing similarities with pseudo gel mapping from the reference strain of Peach X-Disease Phytoplasma (GenBank Accession No. L33733). Nested PCR products from accessions BGM 1526 and BGM 1212 were purified and sequenced by Macrogen, (Seoul, South Korea) in both directions, manually edited, and the consensus sequences were deposited in the NCBI database (GenBank Accession Nos. KF019184 and KF019185). Phylogenetic studies were conducted based on maximum parsimony, neighbor-joining, and maximum likelihood analysis for 16S rRNA. The phytoplasma 16S rRNA gene sequences from both strains had 99% identity (P < 0.0001) with the 16SrIII-L CFSD phytoplasma (EU346761 and AY737647), described by Alvarez et al. (1) infecting cassava in Colombia. To our knowledge, this is the first report of a phytoplasma associated with Cassava Frogskin Disease in Brazil, where only the dsRNA virus was recognized as causing this symptom (3). This is not likely to be an isolated case, and possibly more cassava plants are infected with this phytoplasma in Brazil. Due to the difficulties to observe the symptoms at the field level, this could be an emerging disease in that country.